Pengaruh Disiplin Belajar Terhadap Kemampuan Penalaran Matematis Siswa pada Materi Bangun Ruang - Ivana, Najwa awaa; Sundayana, Rostina; Sri Sumartini, Tina Sri Sumartini (Universitas PGRI Semarang, 2026)
This study aims to assess the level of students' learning discipline, their mathematical reasoning skills, and how much influence these disciplines have on reasoning skills on spatial building materials. Using a quantitative approach, the research design taken is correlational. All grade VIII students at MTs Maarif Sukakarya, Garut Regency, West Java, were involved as a population in this research. Meanwhile, the sample obtained through the purposive sampling method amounted to 28 students. Data collection was carried out using two main instruments, namely a learning discipline questionnaire and a test instrument to measure mathematical reasoning skills. Once the data is collected, the analysis is completed through descriptive and inferential statistical tests. Based on the results of the normality test, it showed an abnormal distribution of data, so the analysis was continued using the Spearman correlation test. The results showed that the level of students' learning discipline was in the medium category with a percentage of 70.58%, while their mathematical reasoning capacity was classified as very good at 84%. The results of the calculation of the Spearman correlation coefficient recorded a value of 0.400 with a significance level of 0.035, indicating a significant relationship between the two variables. This shows that learning discipline has a positive effect on students' overall mathematical reasoning skills.